Does environmental regulation promote the volatility of technological progress? —analysis based on the law of entropy generation - Cao, Jianhong; Siong, Hook Law; Desheng, Wu; Tang, Xianghua; Fan, Yaojun; Xiaodong, Yang (Frontiers Media, 2022)
The existing literature show that there are uncertainty about the impact of environmental regulation on technological progress, and the digital financial inclusion is closely related to environmental regulation and technological progress. Therefore, the aim of this paper is to study the effect of environmental regulation on the volatility of technological progress with digital financial inclusion as the threshold variable by using the System GMM method and the dynamic threshold model. The sample employed in this paper is collected from 30 provinces in China from 2011 to 2018. The findings show that: first, environmental regulation insignificantly promotes the volatility of technological progress; second, the interaction term between environmental regulation and digital financial inclusion significantly inhibits the volatility of technological progress; third, taking digital financial inclusion as the threshold variable, there is an inverted U-shaped relationship between environmental regulation and the volatility of technological progress. In addition, this paper uses the law of entropy generation to explain the theoretical mechanism of this study. The empirical results of this paper emphasize that digital financial inclusion is of great significance to improve the efficiency of China’s environmental regulation and maintain the stability of technological progress, which is conducive to accelerating the green transformation of China’s economy. Therefore, the state should introduce relevant policies to support and promote the digitalization and inclusion of finance, so as to help improve China’s environmental quality.